Implementation of a Decision Support System in Selecting the Best Mid-Range Smartphone Using the Ahp and Moora Methods - Ritonga, Bayu Surbana; Sriani, Sriani (Journal La Multiapp, 2024)
The rapid development of information technology, especially the internet and smartphones, has changed the paradigm in the way humans interact and access information. In Indonesia, internet use has soared, with most access via smartphones. The growth of the mid-range smartphone market creates the need for a more in-depth assessment in selecting suitable products. To help potential buyers, this research proposes the use of a decision support system (DSS) that uses the Analytical Hierarchy Process (AHP) and Multi-Objective Optimization by Ratio Analysis (MOORA) methods. AHP is used to determine the weight of the criteria, while MOORA is used to provide recommendations for smartphone selection. From the test results on 87 types of mid-range smartphones using a combination of these two methods, the recommendation results for mid-range smartphones with the Realme GT Neo 3T brand as first place, Realme GT Neo 3 as second place, and Poco F4 as third place.